EFEKTIVITAS PERATURAN PRESIDEN NOMOR 44 TAHUN 2016 TERHADAP KESEMPATAN KERJA PRODUKTIF BAGI TENAGA KERJA DALAM KEGIATAN PENANAMAN MODAL PADA SEKTOR PERKEBUNAN DI SUMATERA BARAT - Viana, Wira Okta (Universitas Ekasakti, 2018)
Presidential Regulation number 44 of 2016 regulates the list of closed business fields with requirements in the field of investment. The issuance of Presidential Regulation number 44 of 2016 is expected to be implemented effectively and efficiently to the opening of productive employment opportunities for workers in investment activities, especially in the plantation sector in West Sumatera.The issues raised in writing this thesis are: First how the effectiveness of Presidential Regulation number 44 of 2016 on productive employments opportunities for labor in investment activities in West Sumatera. Second the factors that hamper the effectviness of Presidential Regulation number 44 of 2016 on productive employment opportunities for labor in plantation investment activities in West Sumatera. Third how is policy of West Sumatera provincial government related to the effectiveness of presidential regulation number 44 year 2016 in productive employment opportunity for manpower in investment activity in West Sumatera.The research method used in the writing of this thesis is the normative juridical approach supported by empirical juridical approach through interview techniques and date collection techniques by the author at the Office of One Stop Service Integrated Servive Center (DPMPTSP) of West Sumatera Province and the Office of Manpower ang Tranmigration of Sumatera Province West. Based on the results of research and analysis, it can be concluded as follows: First effectiveness Presidential Regulation number 44 of 2016 on productive employment opportunities for labor in plantation investment activities in West Sumatera has been running effectively but still not maximal because it still encountered some obstacles and weaknesses in this Presidential Regulation and its implementation. Second The internal factors included the absence of provisions on the maximum dan minimum limits of plantation land use, business scale, and so forth. External factors included limited land fpr plantations, land with traditional customary community land, low labor human resources, and investment licensing issues that are perceived as inefficient. Third West Sumatera provincial governments have issued regulations stipulated in the Regional Regulation and Governor Regulation which is guided by the provisions of Presidential Regulation number 44 of 2016 and other legislation related to the increase of employment and investment activities, especially the plantation sector in West Sumatera. One of them is Regional Regulation of West Sumatera Province number 2 of 2014 concerning Investment and Regulation of Gubernur of West Sumatera number 70 year 2013 concerning General Plan of Capital Investment of West Sumatera.